Modulation of multidrug resistant in cancer cells by EGCG, tannic acid and curcumin - Li, Hanmei; Krstin, Sonja; Wink, Michael (Phytomedicine, 2018)
Background: Cancer is one of the most common life-threatening diseases worldwide; many patients develop multidrug resistance after treatment with anticancer drugs. The main mechanism leading to multidrug resistance is the overexpression of ABC transporters in cancer cells. Chemosensitizers are needed to inhibit the activity of ABC transporters, resulting in higer intracellular concentration of anticancer drugs. Some secondary metabolites have been reported to be chemosensitizers by inhibiting ABC transporters. Epigallocatechin gallate (EGCG), tannic acid, and curcumin were employed in this study. Different assays were used to detect whether they have the ability to inhibit P-gp activity and overcome multidrug resistance in cancer cells overexpressing P-gp. Hypothesis/Purpose: CEM/ADR 5000 and Caco-2 cell lines, which overexpress P-gp, are multidrug resistant cell lines. We first detected whether the combination of polyphenols (EGCG, tannic acid, curcumin) and doxorubicin, an anticancer drug, is synergistic or not. To further understand the potential mechanism, EGCG, tannic acid, and curcumin were tested to check whether they have the ability to inhibit P-gp activity. When P-gp activity is inhibited, the intracellular concentration of doxorubicin is higher, resulting in enhanced cytotoxicity of doxorubicin. Study design: The P-gp overexpressing human colon cancer cell line Caco-2 and human T-lymphoblastic leukemia cell line CEM/ADR 5000 were used in this study. Two-drug combinations (doxorubicin+polyphenol) and three-drug combinations (doxorubicin+polyphenol+digitonin) were tested to examine potential synergism. The potential mechanism leading to synergism would be the inhibition of P-gp activity. A Rhodamine 123 assay and Calcein-AM assay in Caco-2 and CEM/ADR 5000, respectively, were used to detect P-gp inhibition by EGCG, curcumin, and tannic acid. Methods: MTT assay was used to determine the cytotoxicity of doxorubicin, polyphenols and digitonin alone, and then their combinations. Furthermore, Rhodamine 123 and Calcein-AM were used to detect the effects of polyphenols on the activity of P-gp. Results: The results demonstrated that a combination of non-toxic concentrations of each polyphenol with doxorubicin synergistically sensitized Caco-2 and CEM/ADR 5000 cells. Furthermore, three-drug combinations (doxorubicin+polyphenol+digitonin) were much more effective. In addition, the activity of P-gp in Caco-2 and CEM/ADR 5000 cells was measured. Consistent with the combination results, tannic acid and curcumin decreased the activity of P-gp both in Caco-2 and CEM/ADR 5000. EGCG, which weakly affected the activity of P-gp in CEM/ADR 5000, only had an effect on P-gp under higher concentration in Caco-2 cells. Conclusion: Our results show that EGCG, curcumin, and tannic acid, when combined with doxorubicin, can exert synergism, mediated by a reduced activity of P-gp. This study suggests that polyphenols, by modulating the activity of P-gp, may be used as chemosensitisers.
Gesehen am 11.02.2020